Reexamination of alcohol dehydrogenase structural mutants in Drosophila using protein blotting. - Hollocher, H.; Place, A.R. (Genetics, 1987)
Using protein blotting and an immuno-overlay procedure, we have reexamined the cross-reacting material produced by ADH null-activity mutants generated with ethyl methanesulfonate (EMS). Of the 13 mutants, 11 have an immunodetectable polypeptide of wild-type size. The native and urea denatured isoelectric points (pI) establish that 7 of 13 of the mutations have no effect on protein charge. The electrophoretic mobilities of each variant on increasing percent acrylamide gels (Ferguson analysis), reveal that 9 of the 11 immunodetectable mutants have retained the ability to form dimers under native conditions. None of the inactive mutant proteins has the ability to form the "adduct-bound" isozyme. We have found no correlation between protein pI and in vivo stability. The observed frequencies of specific charge class alterations do not dispute the propensity of G:A transitions previously found for EMS mutagenesis.